Transforming Thai Education with AI to Cultivate Public-Minded Global Citizens - Panlumlers, Kawita; Thangjui, Winaphorn; Namwong, Pornpimon (Research Community and Social Development Journal, 2026)
Introduction: The rapid advancement of Artificial Intelligence (AI) has created new opportunities and challenges for education systems worldwide. In Thailand, persistent issues such as educational inequality, uneven access to quality learning resources, centralized administration, and the need to develop future-ready competencies have intensified the urgency of educational reform. This academic article aims to synthesize current knowledge and conceptual perspectives on the integration of AI into Thai education to cultivate public-minded global citizens who are ethically aware, socially responsible, and capable of engaging constructively in an interconnected world. Subject: The article examines the relationship between AI in education, public-mindedness, and global citizenship education. It discusses how AI can support personalized and adaptive learning, learning analytics, automated assessment, instructional content generation, and inclusive learning for students with diverse needs. At the same time, it emphasizes that AI should not be viewed merely as a technological tool for efficiency, but as a transformative mechanism for promoting equity, learner agency, civic responsibility, and human-centered learning. The article also addresses key ethical considerations, including data privacy, algorithmic transparency, equitable access to AI technologies, AI literacy, and the preservation of the human role of teachers in AI-enhanced learning environments. Conclusion: The synthesis indicates that AI has strong potential to reshape Thai education by enabling more flexible, personalized, and inclusive learning experiences. However, successful integration requires coherent national policies, ethical governance, inclusive digital infrastructure, teacher competency development, and continuous evaluation of both learning outcomes and social impacts. Benefit, Utilization: The article provides a conceptual framework for transforming Thai education with AI to cultivate public-minded global citizens. This framework can be utilized by policymakers, educators, curriculum developers, and educational institutions as a strategic guideline for designing AI-supported learning systems that promote equity, ethical awareness, social responsibility, and sustainable educational development in Thailand.